Alexander Men`s views on doctrinal, moral and ritual content of world religions in light of the teaching of the magisterium of the church = Poglądy Aleksandra Mienia dotyczące doktrynalnej, moralnej i rytualnej treści religii światowych w świetle nauczania magisterium kościoła - Lukaševičius, Arturas (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article presents the analysis of Alexander Men`s views on the doctrinal, moral and ritual content of world religions. His position is assessed in light of the teaching of the Magisterium of the Church on these issues. Working as a priest of the Russian Orthodox Church, Men devoted significant attention to world religions. His most important work in this area is a six-volume history of religions, entitled In Search of the Way, the Truth and the Life. While describing world religions, Men indicates the presence of the semina Verbi, mixed with various religious errors.
Keywords: Mień, Aleksandr Władimirowicz (1935-1990); world religions; Magisterium of the Church; semina Verbi; inter-religious dialogue; religie światowe; Magisterium Kościoła; dialog międzyreligijny